We'll define the point of intersection of the two lines as our origin, which will make this problem a lot easier. The equations of our lines, then, follow: {a
1: y = x√3 {a
2: y = mx, where m is our unknown. Call the origin A. On a
1, the point B will be (1,√3), and the point C on a
2 will be (1,m). From the information given, we determine the following: c = 2 a = |m - √3| b = √(1+m
2) We can quickly apply the law of cosines to solve for m: a
2 = b
2 + c
2 - 2bc cos A (m - √3)
2 = (√(1+m
2))
2 + 2
2 - 2(2)√(1+m
2)(1/7), which reduces to a quadratic equation, 143m
2 + 98m√3 + 45 = 0 In the process of deriving this equation, we have m√3 + 1 =
√(1+m
2), so m >= -
We'll use the quadratic formula to solve for m: m = (-98√3 ± √(98*98*3 - 4*143*45)/(2*143) = (-98√3 ± 32√3)/286 =
or
By inspection, we see that
<
. However, this implies that cos A = -1/7, which means that the supplementary angle of A which is also formed with this intersection, A', exists such that cos A' = 1/7 . Therefore, our two solutions are:
and